2017
DOI: 10.1111/njb.01259
|View full text |Cite
|
Sign up to set email alerts
|

Seed testa micromorphology of thirty‐eight species of Allium (Amaryllidaceae) from central Asia, and its taxonomic implications

Abstract: Micromorphological characteristics of the seed testa of 38 species belonging to 19 sections and seven subgenera of Allium from central Asia have been evaluated with a scanning electron microscope (SEM). Several taxonomically significant characters were found. The results showed that the epidermis consists of polygonal cells with different dimensions, that the cellular arrangement is tight or loose with or without reticulate tissue, and that the arrangement of cells is regular or irregular. The main variation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 28 publications
10
44
0
Order By: Relevance
“…Worldwide, more than 460 taxa of Allium have been investigated for their seed macro- and micro-morphological characteristics [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The highest number of species have been studied from Turkey, China (Xinjiang), and Iran with 62, 38 and 23 species, respectively [ 28 , 31 , 32 ]. The results of this study agree with the former investigations on seed morphology of the genus with respect to their shape, size, and surface sculpture (e.g., Celep et al [ 28 ]; Duman et al [ 29 ]; Choi et al [ 30 ]; Lin and Tan [ 31 ]; Veiskarami et al [ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, more than 460 taxa of Allium have been investigated for their seed macro- and micro-morphological characteristics [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The highest number of species have been studied from Turkey, China (Xinjiang), and Iran with 62, 38 and 23 species, respectively [ 28 , 31 , 32 ]. The results of this study agree with the former investigations on seed morphology of the genus with respect to their shape, size, and surface sculpture (e.g., Celep et al [ 28 ]; Duman et al [ 29 ]; Choi et al [ 30 ]; Lin and Tan [ 31 ]; Veiskarami et al [ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
“…According to Choi et al [ 30 ], the seed testa sculpture attributes in combination with seed shape provide key characteristics to distinguish major clades in the molecular phylogeny in northeastern Asian and northern North American Allium species. Recently, Lin and Tan [ 31 ] studied seed coat characteristics of 39 species that belong to 19 sections of Allium in China (Xinjiang) and divided them into six groups. In addition, Veiskarami et al [ 32 ] investigated seed size and shape as well as micro-morphology of 23 species belonging to two subgenera and six sections in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent taxonomic treatment (Fritsch and Abbasi 2013) Previous morphological and anatomical studies have provided characters useful for separation and delimitation of subgenera, sections and species in Allium. Characters of high taxonomic importance are provided by leaf anatomy (Saghir and Mann 1969, Tanker and Kurucu 1981, Miceli et al 1984, Fritsch 1988, Uysal 1999, Yousaf et al 2008, Özdemir et al 2008, Draghia et al 2013, Mashayekhi and Columbus 2014, Li et al 2010, root anatomy (Uysal 1999, Özdemir et al 2008, Draghia et al 2013), rhizome and bulb anatomy (Jaccard and Frey 1927, Mann 1952, Huang and Sterling 1970, Gregory 1996, Prychid and Rudall 1999, Shrestha 2007, Rola 2014, Khorasani et al 2018, seed morphology (Neshati and Fritsch 2009, Bednorz et al 2011, Celep et al 2012, Lin and Tan 2017, ovary surface micromorphology (Gurushidze et al 2008, Choi et al 2011 and scape anatomy (Jacobsen 1979, Fritsch 1992, 1993, Uysal 1999, Özdemir et al 2008, Hosseinzadeh et al 2009, Miryeganeh and Movafeghi 2009. Previous investigations on the scape anatomy of Allium revealed that the shape and diameter of cross-sections, epidermis posture, thickness of cuticle ...…”
Section: Introductionmentioning
confidence: 99%
“…According to literature data (Pastor , Češmedžiev and Terzijski , Fritsch et al 2006, Neshati and Fritsch 2009, Celep et al 2012, Salmeri et al 2016, Lin and Tan , Özhatay et al 2018), the micro‐sculptures of the seed testa in Allium species are a stable and conservative character, which have relevant taxonomical and phylogenetic implications. Seeds of Allium valdecallosum show a semi‐ovoid shape (3.3 × 2.0–2.2 mm), with a feebly rugose surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a part of biosystematic studies on the species belonging to Allium subgen. Allium in the Mediterranean area (Brullo et al a, b, 1999, 2003, a, b, , 2014, 2017), )a very critical species recorded from a single locality and not recently recollected had to be examined. The species was first described by Maire and Weiller (Maire ) from Morocco and named Allium valdecallosum , due to a callous thickening at the tepal base.…”
Section: Introductionmentioning
confidence: 99%